2010
DOI: 10.1111/j.1474-9726.2010.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Declining expression of a single epithelial cell‐autonomous gene accelerates age‐related thymic involution

Abstract: SummaryAge-related thymic involution may be triggered by gene expression changes in lymphohematopoietic and ⁄ or nonhematopoietic thymic epithelial cells (TECs). The role of epithelial cell-autonomous gene FoxN1 may be involved in the process, but it is still a puzzle because of the shortage of evidence from gradual loss-of-function and exogenous gain-of-function studies. Using our recently generated loxP-floxed-FoxN1(fx) mouse carrying the ubiquitous CreER T (uCreER T ) transgene with a low dose of spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
99
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 43 publications
7
99
0
Order By: Relevance
“…The reduced expression or induced deletion of FOXN1 resulted in reduced TEC number and a disrupted thymic microenvironment [16,18,22,24,27]. Conversely, an intrathymic injection of FOXN1 cDNA-bearing plasmid into the thymus of aged mice or FOXN1 transgenic mice resulted in an increased number of TECs, leading to enhanced thymopoiesis and an increased naïve T-cell output [23,25]. These results indicate that FOXN1 has the potential to be used in the restoration or regeneration of TECs.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…The reduced expression or induced deletion of FOXN1 resulted in reduced TEC number and a disrupted thymic microenvironment [16,18,22,24,27]. Conversely, an intrathymic injection of FOXN1 cDNA-bearing plasmid into the thymus of aged mice or FOXN1 transgenic mice resulted in an increased number of TECs, leading to enhanced thymopoiesis and an increased naïve T-cell output [23,25]. These results indicate that FOXN1 has the potential to be used in the restoration or regeneration of TECs.…”
Section: Introductionmentioning
confidence: 68%
“…Although age-dependent thymic involution can be caused by both ETP and TEC degeneration, recent data have shown that a reduced expression or the deletion of a single gene, FOXN1, leads to phenotypes similar to age-dependent thymic involution. Moreover, overexpression of FOXN1 attenuates age-associated thymic involution [15,23,25]. It will be of much interest to determine whether rFOXN1 treatment can prevent or reverse age-dependent thymic involution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations